2019
DOI: 10.1126/science.aat9691
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage trigger antiviral immunity and prevent clearance of bacterial infection

Abstract: Bacteriophage are abundant at sites of bacterial infection, but their effects on mammalian hosts are unclear. We have identified pathogenic roles for filamentous Pf bacteriophage produced by Pseudomonas aeruginosa (Pa) in suppression of immunity against bacterial infection. Pf promote Pa wound infection in mice and are associated with chronic human Pa wound infections. Murine and human leukocytes endocytose Pf, and internalization of this single-stranded DNA virus results in phage RNA production. This triggers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
369
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 337 publications
(429 citation statements)
references
References 53 publications
18
369
0
3
Order By: Relevance
“…For phages, presuming they act by modulating the bacterial community, the animal model must harbor the relevant bacterial host species, and thus the bacterial microbiome may need to be manipulated as well. Notably, some recent studies have suggested that phages may also interact directly with eukaryotic host cells [28,29]. Overall, significant effort and resources must be expended to establish robust animal-infection models suitable to define the role of the virome.…”
Section: The Need For Experimental Animal-infection Modelsmentioning
confidence: 99%
“…For phages, presuming they act by modulating the bacterial community, the animal model must harbor the relevant bacterial host species, and thus the bacterial microbiome may need to be manipulated as well. Notably, some recent studies have suggested that phages may also interact directly with eukaryotic host cells [28,29]. Overall, significant effort and resources must be expended to establish robust animal-infection models suitable to define the role of the virome.…”
Section: The Need For Experimental Animal-infection Modelsmentioning
confidence: 99%
“…This is the case of parasites that infect other parasites, such as bacteriophage viruses, that can influence the outcome of bacterial infections. For example, in a cohort of individuals with chronic wounds, a report showed that the phage Pf, which coexists with Pseudomonas aeruginosa in infected wounds, triggered the production of type I IFN, the inhibition of tumor necrosis factor (TNF) production, and the suppression of phagocytosis in human primary monocytes and mouse bone marrow-derived macrophages, dampening the antibacterial response and promoting the bacterial infection [60]. However, bacteriophages can also provide protection to the human host by directly attacking pathogenic bacteria and by upregulating in human PBMCs the expression of proinflammatory genes such as IL1A, IL1B, IL6, TNFA, CXCL1, and CXCL5, as shown for several S. aureus and P. aeruginosa phages, including PNM, LUZ19, 14-1, and GE-vB_Pae-Kakheti25 [61].…”
Section: Nonpathogenic Microbes: Mutualistic Bacteria and Virusesmentioning
confidence: 99%
“…Close follow‐up of the effect of phage therapeutic products in the human host is essential. Recent data suggest that phages may be able to produce mRNA within human cells, thereby modulating the immune response of the human host by decreasing tumour necrosis factor production and preventing bacterial clearance …”
Section: Phage Therapymentioning
confidence: 99%
“…29,30 by decreasing tumour necrosis factor production and preventing bacterial clearance. 54 Bacterial resistance to phages is a result of bacterial adaptation to the selective pressure of phage infections. In natural environments, antibiotic and phage resistance phenotypes are thought to evolve independently.…”
Section: Phag E Ther Apymentioning
confidence: 99%